Experimental demonstration of novel end-pumping method for double-clad fiber devices - Peterka, Pavel; Kasík, Ivan; Mat Jec, Vlastimil; Kube Ek, Václav; Dvo A Ek, Pavel (Optics letters, 2006)
We present experimental demonstration of an end-pumping scheme based on splicing the multimode pump and single-mode signal fibers directly to a double-clad fiber with a tailored cross section. The method is used to pump a double-clad, erbium- and ytterbium-doped, fiber ring laser. The efficiency of the end-pumping method is tested by determining the slope efficiencies of the fiber ring laser and the fiber laser in a Fabry-Perot configuration. Comparable slope efficiencies are found when both laser configurations have similar output coupler ratios. The developed pumping scheme and double-clad fiber can find applications in cost-effective power fiber amplifiers and lasers.